Arabidopsis chloroplast quantitative editotype. Issue 9 (21st March 2013) - Ruwe, Hannes; Castandet, Benoit; Schmitz-Linneweber, Christian; Stern, David B.
Abstract : Chloroplast C‐to‐U RNA editing is an essential post‐transcriptional process. Here we analyzed RNA editing in Arabidopsis thaliana using strand‐specific deep sequencing datasets from the wild‐type and a mutant defective in RNA 3′ end maturation. We demonstrate that editing at all sites is partial, with an average of 5–6% of RNAs remaining unedited. Furthermore, we identified nine novel sites with a low extent of editing. Of these, three sites are absent from the WT transcriptome because they are removed by 3′ end RNA processing, but these regions accumulate, and are edited, in a mutant lacking polynucleotide phosphorylase. Abstract : We investigated chloroplast C to U editing by strand‐specific RNA‐seq. Nine novel editing sites were identified. Three novel editing sites are only detectable in a mutant lacking polynucleotide phosphorylase. Novel sites are edited to a low extent.